Effectiveness of travel restrictions in the rapid containment of human influenza: a systematic review - Mateus, Ana; Otete, Harmony E.; Beck, Charles R.; Dolan, Gayle P.; Nguyen-Van-Tam, Jonathan S. (World Health Orgainization, 2014)
OBJECTIVE: To assess the effectiveness of internal and international travel restrictions in the rapid containment of influenza.